Cis-Regulatory Elements and Trans-Acting Factors Modulating Post-Transcriptional Splicing in Cancer: A Short Communication - Ur Rehman, Shafee (Bangladesh Journal of Medicine, 2025)
The key post-transcriptional process of alternative splicing (AS) generates transcriptomic and proteomic diversity through its mechanism. The precise regulation of AS depends on cis-regulatory RNA elements together with trans-acting protein factors whose alterations frequently occur in cancer cases. Cancer progression occurs through the generation of abnormal isoforms which emerge from mutations together with altered splicing factors and epigenetic transformations. The combination of modern sequencing approaches with computational tools allows scientists to study cancer-specific splicing patterns which enables both biomarker development and targeted therapeutic applications. This paper discusses the basic molecular mechanisms behind AS control as well as cancer-related abnormalities and new precision oncology therapeutic approaches through splice-switching oligonucleotides and smallmolecule modulators and CRISPR-based strategies. Bangladesh J Medicine 2025; 36(3): 142-146